2013
DOI: 10.1155/2013/305874
|View full text |Cite
|
Sign up to set email alerts
|

Human Influences on Tree Diversity and Composition of a Coastal Forest Ecosystem: The Case of Ngumburuni Forest Reserve, Rufiji, Tanzania

Abstract: This paper reports on the findings of an ecological survey conducted in Ngumburuni Forest Reserve, a biodiversity rich forest reserve within the coastal forests of Tanzania. The main goal of this study was to determine the influence of uncontrolled anthropogenic activities on tree species diversity and composition within the forest ecosystem. It was revealed that economic activities including logging, charcoaling, and shifting cultivation were the most important disturbing activities affecting ecological funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
0
19
1
Order By: Relevance
“…Miombo woodland dynamics is strongly influenced by anthropogenic factors [6][7][8] and most ecosystems are being threatened by the increased demand for services by the burgeoning human population [9]. Woodland ecosystems and their valuable biodiversity resources are being lost at an accelerated rate [10][11][12], thereby altering ecosystem function and consequently threatening the provision of services and goods especially to poor rural communities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Miombo woodland dynamics is strongly influenced by anthropogenic factors [6][7][8] and most ecosystems are being threatened by the increased demand for services by the burgeoning human population [9]. Woodland ecosystems and their valuable biodiversity resources are being lost at an accelerated rate [10][11][12], thereby altering ecosystem function and consequently threatening the provision of services and goods especially to poor rural communities [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results of their study showed that logging had a negative influence on species richness. Also, the study conducted by Kimaro and Lulandala (2013) revealed that logging, charcoaling, and shifting cultivation affected biodiversity integrity of the forests, The authors report that values of species diversity and composition within the undisturbed forest areas were significantly different from the corresponding values in heavily disturbed areas.…”
Section: Introductionmentioning
confidence: 99%
“…Different processes and activities occurring in forest ecosystems affect forest structural parameters by providing favorable or unfavorable conditions [2,6]. Disturbances affect the ecological relationship between forest vegetation and soils [8,9,10,11]. In essence, human induced disturbances bring soil degradation, which is defined in this study as any physical or chemical alteration of the soils caused by different operations in forest ecosystems [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a strong relationship between disturbances on plant species composition and impacts on soil parameters [18,19]. Understanding the impacts of human activities on the coastal forests of Tanzania is crucial because these activities have affected the structure and biodiversity of these forests for more than 50 years [8]. It is obvious that human activities affected the coastal biodiversity, which is composed of over 10,000 plant species, hundreds of which are recognized as nationally endemic [20,21,22].…”
Section: Introductionmentioning
confidence: 99%